2015
DOI: 10.1177/1534508415579095
|View full text |Cite
|
Sign up to set email alerts
|

Technical Adequacy and Acceptability of Curriculum-Based Measurement and the Measures of Academic Progress

Abstract: Curriculum-based measurement in reading (CBM-R) and the Measures of Academic Progress (MAP) are assessment tools widely employed for universal screening in schools. Although a large body of research supports the validity of CBM-R, limited empirical evidence exists supporting the technical adequacy of MAP or the acceptability of either measure for universal screening. Purposes of the current study were to replicate and extend prior research by (a) examining the extent to which CBM-R performance measures more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
3
14
0
2
Order By: Relevance
“…Rather, fall and spring MAP scores and previous year’s scores on the MCA-III had the strongest relationship with performance on the statewide assessment. This finding is similar to that of a study regarding the relationship between CAT and statewide assessments conducted by January and Ardoin (2015) who found that CAT predicted performance better on statewide assessments as compared with traditional CBM. This is consistent with other research as well.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rather, fall and spring MAP scores and previous year’s scores on the MCA-III had the strongest relationship with performance on the statewide assessment. This finding is similar to that of a study regarding the relationship between CAT and statewide assessments conducted by January and Ardoin (2015) who found that CAT predicted performance better on statewide assessments as compared with traditional CBM. This is consistent with other research as well.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with other research as well. For example, CAT may be able to predict performance better than other screening measures because a student’s achievement level can be identified quicker with a smaller standard error (January & Ardoin, 2015; McFadden et al, 2001; van der Linden & Glas, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Strong associations between MAP and the state assessment corroborate previous research of strong associations between MAP and other standardized assessments of reading achievement (Ball & O'Connor, 2016;January & Ardoin, 2015;Klingbeil et al, 2015Klingbeil et al, , 2017. However, the concurrent relation between MAP and the standardized assessment was slightly lower than findings from the one previous study that evaluated concurrent validity with a norm-referenced assessment (January & Ardoin, 2015).…”
Section: Classification Accuracy Of Step and Mapsupporting
confidence: 83%
“…Next, hierarchical linear regression was used to determine the shared and unique variance of screening measures in relation to the Georgia Milestones. MAP was entered first because it shares the characteristic of being a computer-administered assessment, is convenient to employ, is supported by an emerging peer-reviewed literature base (e.g., Ball & O'Connor, 2016;January & Ardoin, 2015;Klingbeil et al, 2017), and has content overlap with the Georgia Milestones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation